2015
DOI: 10.1002/lsm.22449
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term microbiological effects of photodynamic therapy in non‐surgical periodontal treatment of residual pockets: A split‐mouth RCT

Abstract: The combined therapeutic approach SRP + PDT may reduce A. actinomycetemcomitans levels for a short-term period, associated with additional improvement in clinical parameters in treating residual pockets. Lasers Surg. Med. 48:944-950, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
0
47
0
2
Order By: Relevance
“…The present study found a significant decrease in prevalence of these bacterial species after the application of LLLT + SRP therapy, but not when only SRP was performed. Corrêa et al 's results are in agreement with our findings that significant reduction in mean prevalence of A. actinomycetemcomitans was found at LLLT‐treated sites, especially in the first reevaluation periods (3 and 7 days after therapy). Likewise, an additional reduction in some of these pathogens after adjunctive LLLT could be considered as a positive aspect and a possible benefit for the future maintenance of these results.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a significant decrease in prevalence of these bacterial species after the application of LLLT + SRP therapy, but not when only SRP was performed. Corrêa et al 's results are in agreement with our findings that significant reduction in mean prevalence of A. actinomycetemcomitans was found at LLLT‐treated sites, especially in the first reevaluation periods (3 and 7 days after therapy). Likewise, an additional reduction in some of these pathogens after adjunctive LLLT could be considered as a positive aspect and a possible benefit for the future maintenance of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence of the short‐term benefits of PDT to reduce bacterial counts, it might be useful as an initial treatment for suppressing the proliferation of bacteria, and adding the frequencies of application may lead to a more effective and satisfying result. This is also suggested by Corrêa et al that single‐episode PDT may not be sufficient, investigations on multiple courses effects are needed.…”
Section: Discussionmentioning
confidence: 91%
“…Both treatment modalities being applied in this study led to significant decreases in the levels of all periodontopathogens. However, it was not possible to completely eliminate these microorganisms even from the sites assumed clinically healthy after treatment . Mechanical instrumentation decreases the subgingival microbial load and a microflora compatible with periodontal health is obtained .…”
Section: Discussionmentioning
confidence: 99%
“…PDT has a lethal effect against periodontopathogens as shown in a number of experimental and also clinical studies in humans . Qin et al demonstrated that total bacterial flora and clinical signs of periodontal inflammation could be reduced by toluidine blue O‐mediated photoinactivation in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation